Upwind scheme to solve time-periodic temperature effect on convective nanofluid flow in a square cavity - Bendaraa, A.; Charafi, M. M.; Hasnaoui, A. (European physical journal plus, 2022)
The phenomenon of natural convection of copper–water nanofluid inside a square cavity with time-periodic temperature is studied numerically. The studied configuration is subjected to a temperature gradient, with the bottom wall ( y = 0) maintained to cold temperature and the top one ( y = L ) subject to a periodic temperature. The other walls, at x = 0 and x = L , are adiabatic. Dimensionless governing equations formulated using stream function, vorticity, and temperature have been solved by finite difference method, where the upwind scheme was employed. The studied configuration is similar to a cooling block that follows the solar panel in these different inclinations. The objective of the study is to predict the behaviour of this block filled with copper-based nanofluids in the cooling of the solar device. A calculation code was performed to analyse the effect of Rayleigh number (Ra), the oscillations frequency ( f ), the effect of cavity inclination angle, and nanoparticle suspension rate on fluid flow and heat transfer as well as the appearance of cooling periods. It has been found that a good intensification of heat transfer is directly related to the increase in Rayleigh number and the increase in the frequency of temperature oscillation, which is considered a very good control parameter that intensifies convective flow and heat transfer.